Independent Energy Program to Overcome Electricity Limitations and Support Digital School Management in Pulau Sembilan, Sinjai. - Nurwidyayanti Nurwidyayanti; Andi Irwandi; Suryani Syahrir; Ahmad Swandi; Fina Melani Putri (SWAGATI : Journal of Community Service, 2026)
This Community Service Program (PKM) was implemented in response to limited electricity access and low utilization of information technology in schools located in island regions. These conditions resulted in restricted use of ICT devices, high operational costs due to dependence on generators, and low digital literacy among teachers. The program aimed to provide an alternative energy solution through the installation of a 600 Wp Solar Power Plant (PLTS) while simultaneously enhancing teachers’ digital capacity to support technology-based school management. The implementation methods included socialization, PLTS installation, technical training on solar energy system maintenance, and training on the use of digital media for school administration and learning. The results indicate that the school now has a stable, cost-efficient, and environmentally friendly electricity source. Teachers are able to independently operate and maintain the PLTS and produce at least three digital media products per school, such as learning websites, interactive applications, and animated presentation media. The program has improved school management efficiency, diversified learning quality, and increased student motivation. In addition to providing direct benefits, it has raised awareness of renewable energy importance in island communities and holds strong potential for replication in other island areas.